Clinical significance of histopathological features of paired recurrent gliomas: a cohort study from a single cancer center - Cong Li; Shaoyan Xi; Yingshen Chen; Chengcheng Guo; Ji Zhang; Qunying Yang; Jian Wang; Ke Sai; Jing Zeng; Jing Wang; Zhiqiang Zhang; Chao Ke; et al. (BMC Cancer, 2023)
Abstract Objective To explore the histopathological characteristics of paired recurrent gliomas and their clinical significance. Methods Glioma patients who received both primary surgery and reoperation when recurrence at Sun Yat-sen University Cancer Center from June 2001 to June 2019 were enrolled. Clinical and pathological characteristics were analyzed retrospectively, and histopathology of reoperation specimens was divided into three categories according to tumor cell activity and the degree of necrosis: active group, low-activity group, and necrosis group. Results A total of 89 patients were included in this study. The 2016 WHO grade of the first operation pathology and IDH1 status were related to survival time after the first operation, but there was no significant association with survival time after reoperation. The time interval between primary and reoperation was shorter for primary high-grade glioma and/or IDH1 wild-type tumor patients than for low-grade glioma and/or IDH1 mutant tumor patients (P < 0.001). Histopathological types of recurrent gliomas were analyzed, and 67 cases (75.3%) were classified into the active group, 14 (15.8%) into the low-activity group, and 8 (8.9%) into the necrosis group. The low-activity or necrosis group was associated with a higher radiotherapy dose and shorter operation interval. Further univariate and multivariate Cox survival analyses showed the histopathological patterns of recurrent gliomas to be related to survival time after reoperation. Conclusion Primary WHO low grade or IDH1 mutant gliomas appeared survival benefit mainly on later recurrence, but was not a prognostic predictor following recurrence. Histopathological feature of recurrent glioma is related to previous treatment, including radiotherapy dosage and chemotherapy treatment, and is also an important independent prognostic factor for patients after reoperation.